(untitled) (Research, Society and Development, 2026)
Contemporary education faces significant challenges, particularly with regard to the search for innovative teaching strategies in Biology education. The use of pedagogical practices that articulate science and art is highly important for the development of the teaching–learning process in this field. In this context, the objective of this study was to analyze the use of cordel literature as a didactic tool in addressing the topic of levels of organization of living beings. The study was conducted with students from the Federal Institute of Pernambuco (IFPE), within the Environmental Management subject of the Technical Course in Hospitality. The proposed activity was carried out in three stages: i) introduction of the topic through the recitation of a cordel pamphlet; ii) discussion of the theme based on a revisitation of each stanza of the cordel; and iii) evaluation of the proposal by the participants. The analysis of the results showed that the use of cordel literature increased student engagement, fostering active participation in the activity. The rhythmic and imagistic characteristics of the cordel contributed to memorization and to the conceptual organization of the content addressed. Therefore, cordel literature is considered an effective didactic resource for approaching topics related to Biology.